Urgensi Penerapan Behavior Based Safety (BBS) dalam Menanggulangi Perilaku Tidak Aman: Studi Kasus di PT X - Salsabil Nabila Azzahra; Nur Fitrah Mahrani; Dafa Cetta Ugama; Muhammad Rifqy; Aditya Wahyu Pratama; Robiyal Dwi Setiawan; Anis Rohmana Malik (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Workplace accidents are often caused by unsafe behavior exhibited by workers. Traditional approaches such as safety training and the use of personal protective equipment (PPE) alone are not sufficient to sustainably change worker behavior. Therefore, the implementation of Behavior Based Safety (BBS) has become an increasingly relevant solution to reduce accident risks by focusing on behavior modification through observation, feedback, and active worker participation. Studies have shown that BBS can reduce workplace accidents by up to 50% through systematic approaches such as positive reinforcement and the development of a safety culture. Its success depends on management commitment, worker engagement, and an appropriate reward system. The implementation of BBS not only improves safety but also enhances operational efficiency. This study aims to analyze the urgency of applying BBS in reducing unsafe behavior in the workplace, as well as the supporting and inhibiting factors influencing its effectiveness. The results indicate that the success of BBS depends on strong leadership, open communication, and a well-designed reward system.